2007
DOI: 10.1095/biolreprod.106.056895
|View full text |Cite
|
Sign up to set email alerts
|

Production of Functional Spermatids from Mouse Germline Stem Cells in Ectopically Reconstituted Seminiferous Tubules1

Abstract: Testicular germ cell transplantation into the seminiferous tubules is at present the only way to induce spermatogenesis from a given source of spermatogonial stem cells. Here we show an alternative method that harnesses the self-organizing ability of testicular somatic cells. The testicular cells of embryonic or neonatal mice or rats and of newborn pigs were dissociated into single cells. Each of them reorganized into a tubular structure following implantation into the subcutis of immunodeficient mice. When mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
82
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 87 publications
(94 citation statements)
references
References 27 publications
12
82
0
Order By: Relevance
“…We showed earlier that spermatogenesis of mice and rats can take place in seminiferous tubules, which were reconstituted subcutaneously from dissociated embryonic or neonatal testicular cells [18]. We found that, once dissociated into single cells, a few testicular germ cells were integrated again in the reconstituted seminiferous tubules.…”
Section: Discussionmentioning
confidence: 64%
See 3 more Smart Citations
“…We showed earlier that spermatogenesis of mice and rats can take place in seminiferous tubules, which were reconstituted subcutaneously from dissociated embryonic or neonatal testicular cells [18]. We found that, once dissociated into single cells, a few testicular germ cells were integrated again in the reconstituted seminiferous tubules.…”
Section: Discussionmentioning
confidence: 64%
“…The integrated GS cells differentiated to round spermatids. Such spermatids were shown to be fertilization-competent by microinsemination into oocytes to deliver normal pups [18].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nonetheless, it has not yet been possible to induce spermatogenesis from these cells in vitro. To produce sperm from GS cells, we had to resort to systems using in vivo conditions such as cell transplantation in the seminiferous tubules 13 , or a method using the reconstructive nature of immature testicular cells 14 . These in vivo methods are useful for certain purposes, such as to test the functional properties of SSCs.…”
mentioning
confidence: 99%